Regulation of submaxillary gland androgen-regulated protein 3A via estrogen receptor 2 in radioresistant head and neck squamous cell carcinoma cells. Issue 1 (December 2017) - Grünow, Jennifer; Rong, Chao; Hischmann, Jan; Zaoui, Karim; Flechtenmacher, Christa; Weber, Klaus-Josef; Plinkert, Peter; Hess, Jochen
Abstract Background Molecular mechanisms of intrinsic or acquired radioresistance serve as critical barrier for curative therapy of head and neck squamous cell carcinoma (HNSCC) and remain a major obstacle for progression-free and disease-specific survival. Methods HNSCC cell lines were treated with a protocol of fractionated irradiation (IR, 4× 2Gy) alone or in combination with antagonists of estrogen receptor signaling and viability was determined by a colony-forming assay (CFA). Expression of submaxillary gland androgen-regulated protein 3A (SMR3A) and estrogen receptor 2 (ESR2) were assessed in tumor cells in vitro by RQ-PCR, Western blot analysis and immunofluorescence staining, and by immunohistochemical staining of tissue microarrays containing tumor sections from patients with oropharyngeal squamous cell carcinoma (OPSCC), which were treated by definitive or adjuvant radiotherapy. Subgroups with distinct SMR3A and ESR2 expression patterns were correlated with clinical parameters and survival outcome including multivariable analysis. Results Fractionated irradiation (IR) revealed an accumulation of tumor cells with prominent SMR3A expression, which was accompanied by an up-regulation of the estrogen receptor 2 (ESR2). ESR2-dependent regulation of SMR3A was supported by induced expression after stimulation with estradiol (E2), which was impaired by co-treatment with 4-Hydroxytamoxifen (TAM) or Fulvestrant, respectively. Both drugs significantly sensitized FaDu cells to fractionated IR as determined by a CFA and accelerated apoptosis. These data suggest a critical role of ESR2 in radioresistance and that SMR3A might serve as a surrogate marker for active ESR2 signaling. In line with this assumption, ESR2-positive oropharyngeal squamous cell carcinoma (OPSCC) with high SMR3A expression had an unfavorable progression-free and disease-specific survival as compared to those tumors with low SMR3A expression. Conclusions In summary, our findings provide compelling experimental evidence that HNSCC with SMR3A and ESR2 co-expression have a higher risk for treatment failure and these patients might benefit from clinically well-established drugs targeting estrogen receptor signaling.